Prescription audit of patients attendees in public health facilities in Maharashtra, India with special reference to rational use of antibiotics - Gawande, Uddhao; Deshmukh, Sona; Kadam, Suhas; Potdar, Gurudatt; Salvitthal, Hrushikesh (International Journal of Research in Medical Sciences, 2017)
Background: As soon as a doctor examines the patient, he/she writes the treatment for the illness on a piece of paper and that is called as “Prescription”. Prescription is a document through which doctor, patient and pharmacist are communicated to each other but many a times if these documents are not properly written or misinterpreted it can affect management of patients. World Health Organization (WHO) has established prescribing indicators to analyze the prescription and promoted rational use of drugs and better management of patients. Prescription audit captures the current practices and identifies opportunities for improvement in patient care and along with the mechanisms for realizing them. The main objective is to analyze the prescription of drugs given to the patients in OPD and IPD of the primary and secondary level public health facilities in Maharashtra. Methods: The study was a cross-sectional and observational based on both qualitative and quantitative data. It comprises of secondary data obtained from copies of prescription collected from selected Rural Hospitals (RHs)/Sub-district Hospitals (SDHs) and District Hospitals (DHs)/ Women Hospitals (WHs) of Maharashtra comprising on prescribing practice, rational use of drugs and antibiotics, patient care and facility specific indicators. The Prescribing patterns were analyzed using WHO guidelines with regard to prescribing, patient care and health facility indicators. Qualitative) data collected on perceptions of the patients attending OPD as regard of doctor’s consultation and dispensing of medicine; as well as perceptions of pharmacists regarding working environment that measures the ability to prescribe drugs rationally. The copies of the prescriptions from the patients attending OPD / IPD at the above mentioned public health institutions (PHCs, RHs, SDHs and DHs/ DWHs) were obtained. Statistical analysis of study was analyzed using the frequencies and cross tabs by using MS-Office Excel and SPSS Version 20. Results: This exercise showed that there is a scope for improvement in prescribing patterns in areas of writing generic names of drugs, essential drugs, writing legible and complete prescriptions. Conclusions: The present study clearly indicates that there is a great need of interventions like distribution of antibiotic guidelines and running workshops and seminars on rational drug use to prescribers to improve the prescribing behaviour in the state of Maharashtra. This can be enforced through introducing such concepts and those of rational prescribing in curriculum of medical schools. E-prescriptions can be started in E-Aushadhi software with periodic clinical meetings to learn from the evidence.